ANALISIS PELAPORAN KINERJA PADA DINAS KEBUDAYAAN DAN PARIWISATA PROVINSI JAWA TIMUR - Huda, Miftakhul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out, to analyze and to evaluate the performance of Department of Culture and Tourism of the East Java Province reviewed from the culture and tourism strategic development which is carried out at the Department of Culture and Tourism of the East Java Province. This research is entitled âThe Analysis of Performance Reporting at Department of Culture and Tourism of the East Java Provinceâ. This research is qualitative descriptive research which is required to explain the study units which are the smallest units of research object which is wanted by the researcher as the classification of data collection and it provides description which is in appropriate with the facts which occur at the time when the research is conducted. The result of the research can provide explanation that Department of Culture and Tourism of East Java Province can improve capabilities in managing the value and cultural diversity as well as to carry out revitalization and actualization of the values of local wisdom which is originated from cultural experience and knowledge which is adjusted with the needs of era in order to strengthen and solidify the nation cultural resilience. The Department of Culture and Tourism of East Java Province can improve the management, protection, development and utilization of cultural asset so it can function optimally as the facility of cultural development, education and recreation. The Department of Culture and Tourism of East Java Province can develop a competitive and qualify cultural destination. The Department of Culture and Tourism of East Java Province can improve the tourism image which is competitive and positive. The Department of Culture and Tourism of East Java Province can improve the quality and the quantity of the human resources, and other supportive products. The Department of Culture and Tourism of East Java Province can carry out the cultural value development program, the cultural asset management program, the cultural diversity management program, the tourism destination development program, the tourism marketing development program, the cultural and tourism management program in appropriate with the expectation of The Department of Culture and Tourism of East Java Province.